Growth rate effects on the thermoelectric performance of CaMnO3-based ceramics. Issue 14 (November 2019) - Ferreira, N.M.; Neves, N.R.; Ferro, M.C.; Torres, M.A.; Madre, M.A.; Costa, F.M.; Sotelo, A.; Kovalevsky, A.V.
Abstract: CaMnO3 –based materials represent a promising family of n-type oxide thermoelectrics. The objective of the present work is assessing the impacts on relevant structural, microstructural and thermoelectric properties of manganites when they are processed by the laser floating zone technique. For this purpose, donor-doped Ca0.9 La0.1 MnO3, CaMn0.95 Nb0.05 O3 and undoped CaMnO3 were used. Different growth conditions have been evaluated through combined studies of structural, microstructural, and thermoelectric characteristics. Despite the presence of secondary phases, electrical resistivity is among the best reported in the literature (9 mΩ.cm at 800 °C for La-doped materials grown at 200 mm/h). Essentially high absolute Seebeck coefficient of 320 μV/K at 800 °C was observed for undoped samples grown at 10 mm/h. Power factor is significantly affected by the growth conditions, reaching the highest values when using the lowest pulling rates. Exceptionally high PF (0.39 mW/K 2 m at 800 °C) was obtained for undoped CaMnO3 samples grown at 10 mm/h.